Geological Hazards in Loess Induced by Agricultural Irrigation in Arid and Semiarid Regions of China - Yuan-jun Xu; Jia-ding Wang; Tian-feng Gu; Jia-xu Kong (Advances in Civil Engineering)
The development of agriculture in the arid and semiarid regions of China mainly depends on agricultural irrigation. Until 2016, water required for agricultural irrigation has accounted for more than 90% of the total water consumption. But traditionally extensive broad irrigation causes frequent loess geological hazards in irrigation area and it threatens security of local life and property. In this paper, we selected the Heifangtai irrigation district in Yongjing County, Gansu Province, where frequent instabilities occur, as the study area. We used laboratory tests and numerical simulation to examine the mechanism of loess landslides owing to the irrigation hydrological cycle. Irrigation changes the local natural hydrogeological conditions because of the loose and macroporous structure of loess. The numerous pores and fissures constitute preferential migration pathways of irrigation water; thus, irrigation can increase the groundwater level and hydraulic gradient. Broad irrigation is the main inducing factor of geological hazards (including landslides, collapses, and soil salinization) in arid and semiarid regions, and the development of fissures and sinkholes increases the risk of landslides. New water-saving irrigation methods need to replace the traditional irrigation methods and improve the utilization of water resources. A monitoring and warning system in susceptible areas should be established to ensure the sustainability of local agriculture.